Mekanisme Pemberhentian Sementara Jabatan Notaris (Studi Putusan Pengadilan Tata Usaha Negara No.88/G/2017/PTUN-JKT) - Mirawati, Lintang; Soepanji, Kris Wijoyo (Universitas Ekasakti, 2023)
The mechanism for granting sanctions imposed by the Notary Supervisory Board to Notaries who violate office regulations must be based on what has been regulated in the applicable laws and regulations. This is because the appropriate mechanism will provide legal certainty for the implementation of the Notary position. This study aims to analyze how the mechanism for temporary termination of notary positions, especially in MPPN RI Decision Number 03/B/MPPN/III/2017 in PTUN Decision No.88/G/2017/PTUN-JKT. In this study, the author uses a form of normative juridical research with the type of research used is descriptive research. The type of data used in this study comes from secondary data in this case is data obtained by the author from the literature study. Based on the results of this study, it is concluded that the mechanism for temporary termination of notary positions is one form of sanctions given by MPP where the temporary suspension must be followed up by MPP to the Minister of Law and Human Rights. MPPN RI Decision Number 03/B/MPPN/III/2017 in PTUN Decision No.88/G/2017/PTUN-JKT regarding the temporary suspension of Notary Achmad Munif there is a mechanism that is not heeded by MPP as mandated in UUJN and Permenkumham. So it can be said that the MPP decision as an individual and concrete norm in its determination is contrary to the norm above it.